PENYEBARAN SEMUT PADA HUTAN LINDUNG SIRIMAU KOTA AMBON - Latumahina, Fransina Sarah; Musyafa, Musyafa; Sumardi, Sumardi; Putra, Nugroho Susetya (Bumi Lestari, 2016)
The experiment was conducted at residential areas Sirimau forest with three sampling methods, which were hand collecting, bait trap (sugar and tuna) and pitfall traps from July to September 2011. The study aims to determine diversity of ants in residential areas in Ambon Sirimau Protected Forest areas. The results of study found 16 species of ants in total reaching 14.913. The most dominant types are Odontoponera denticulata, Pheidole megacephala, Technomyrmex albipes, Tetramorium simillimum, Tetramorium bicarinatum, Tapinoma melanocephalum, Paratrechina longicornis and Anoplolepis gracilipes. Total diversity of ants is 2.789 classified as moderate by spread of number of individual spread and of community stability. The diversity of ants is strongly influenced by light intensity, temperature, humidity, wind, water and season. Difference of temperature micro, light climate, humidit, interspecific competition, availability of variety of food sources, habitat quality and human activities also affect the diversity of ants. Another finding showed invasive ants, they were Soleonopsis geminate, Paratrechina longicornis and Anoplolepis gracilipes.
Keywords: diversity of ants, invasive species, protected areas, settlement area